Body composition assessment and Mediterranean diet adherence in U12 Spanish male professional soccer players: Cross-sectional study - Santos-Sánchez, G.; Cruz-Chamorro, I.; Perza-Castillo, J. L.; Vicente-Salar, N. (Nutrients, 2021)
Abstract: Soccer is the most practiced team sport in the world. Due to the importance of nutrition in soccer performance, controlling the body composition and dietary guidelines of players takes place starting from lower categories. The objective of this study was to evaluate body composition and adherence to the Mediterranean diet of U12 players from a professional soccer team and to identify their dietary weak points. Seventy-one U12 male soccer players participated in the study. Weight, height, percentiles, skinfolds, and body fat were measured by a certified anthropometrist following the procedures recommended by the International Society for the Advancement of Kinanthropometry. The Mediterranean diet adherence test (KIDMED) was the questionnaire used to evaluate eating habits. In addition, a comparison was made among field positions. The results showed percentiles and body fat percentages appropriate for their age. Furthermore, the average score on the KIDMED test showed that the players generally adhered well to the Mediterranean diet, although they should improve their consumption of fruits and vegetables, as well as avoid skipping breakfast. Moreover, goalkeepers and defenders had a higher percentile BMI and percentage of fat than midfielders and forwards. In addition, these players had lower KIDMED values than midfielders and forwards. Although U12 soccer players have an appropriate body composition and adherence to the Mediterranean diet, there are differences between the different field positions that should be assessed by coaches, doctors, and nutritionists/dietitians.